Illusionary delusions. Willingness to exercise self-control can mask effects of glucose on self-control performance in experimental paradigms that use identical self-control tasks - Chatzisarantis, Nikos; Hagger, Martin (Academic Press, 2015)
The purpose of the present article is to highlight limitations of Lange and Eggert's methodology of using identical self-control tasks in testing effects of glucose on depletion of self-control resources and self-control performance. We suggest that when participants engage in two identical self-control tasks, cognitions developed during initial act of self-control may mask the effects of glucose on self-control performance by undermining willingness to exert effort during the second act of self-control. As a consequence, glucose may increase ability to exercise self-control but participants may not want to capitalize on this "ability advantage" because they are unwilling to exercise self-control. The present article concludes that researchers who test the glucose hypothesis in the context of a depletion paradigm should employ dissimilar acts of self-control and ensure that depleted participants are sufficiently motivated to exercise self-control.